Characterization and verification of a two-body wave energy converter with a novel power take-off. (January 2021) - Li, Xiaofan; Martin, Dillon; Liang, Changwei; Chen, ChienAn; Parker, Robert G.; Zuo, Lei
Abstract: The lack of high efficient, predictable, and reliable power take-off (PTO) systems limits developments of ocean wave energy technology. In this paper, a two-body self-reacting wave energy converter (WEC) with a novel PTO is designed, modelled and implemented for efficiency enhancement. A novel mechanical motion rectifier (MMR) using a ball screw mechanism and an enclosed gear set is integrated to improve the energy harvesting efficiency and reliability by rectifying the oscillatory wave motion into unidirectional rotation of the generator. Detailed design and dynamic modelling for the proposed WEC are presented. A prototype of the PTO is tested in a dry lab to characterize and refine the dynamic modelling. The characterized PTO model is combined with the WEC model to create an overall system model. A water tank test is conducted to verify the overall system dynamics, which proves the accuracy of the model and shows the advantages of the proposed WEC on efficiency and predictability. Following the method of how the WEC system is characterized, performance prediction of the proposed WEC with MMR PTO can be achieved with high accuracy. Highlights: Design of a two body wave energy point absorber with a novel power take-off. Characterized the power take-off with bench test and refined the dynamic modeling. Verified the performance of the point absorber through wave tank test.